2018
DOI: 10.1021/acs.jnatprod.7b01036
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Diterpenoids from Jatropha gossypiifolia: Cell Cycle Arrest and Apoptosis-Inducing Activity in RKO Colon Cancer Cells

Abstract: Nine new minor diterpenoids, jatrogossones A-I (1-9), and six known analogues (10-15) were separated from an extract of the branches and leaves of Jatropha gosspiifolia. Compounds 4-6 and 10, possessing a 5/11 fused-ring skeleton, and 8, 9, and 13, with a 5/9/5 fused-ring skeleton, represent rare diterpenoid skeletons that have been found only in compounds isolated from plants of the Jatropha genus. The absolute configurations of 1-10 were defined by using a combination of electronic circular dichroism data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In addition, SAR1B mRNA expression was 7.23-fold higher than the level of GADPH in RKO cells, which was consistent with HCT116 and SW620 cells. The present study selected RKO cells for the validation of functional importance of SAR1B in CRC, which has been widely used in previous CRC studies ( 23 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, SAR1B mRNA expression was 7.23-fold higher than the level of GADPH in RKO cells, which was consistent with HCT116 and SW620 cells. The present study selected RKO cells for the validation of functional importance of SAR1B in CRC, which has been widely used in previous CRC studies ( 23 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…The NOE interaction of H-4/H 2 -7 indicated that C-7–C-8 bond was α-orientationally bridged between C-6 and C-9. Configuration of Δ double bond was assigned as Z by NOE cross-peak of H-11/H 3 -20. Finally, the structure of 1 was secured by a single-crystal X-ray diffraction, which also allowed the determination of its absolute configuration as 2 S ,3 S ,4 S ,6 R ,9 S ,13 R ,15 R with the Flack parameter = 0.02(6) (see Figure , given later in this work).…”
mentioning
confidence: 99%
“…Based on the coisolated major component euphorbia factor L 3 ( 3 ), a putative biosynthetic pathway for euphohyrisnoids A ( 1 ) and B ( 2 ) was proposed in Scheme . Briefly, 3 underwent acid-mediated cyclopropane-opening (C-10–C-11 cleavage), followed by elimination of H-9 to afford an intermediate i with a 10,11- seco -lathyrane skeleton . The keto–enol tautomer of i ( ii ) further underwent an intramolecular Diels–Alder reaction between the terminal double bond C-6C-17 and the diene system C-12C-11–C-9C-10 to give intermediate iiia , constructing the tricyclo­[7.2.2.0 1,7 ] ring system.…”
mentioning
confidence: 99%
“…The most representative components of D. genkwa are the daphnane-type diterpenes, which show various biological activities, including antineoplastic, antileukemic, antifertility, , and skin-irritant activities . As part of our screening program to explore antineoplastic compounds from natural sources, the petroleum ether extract of D. genkwa showed cytotoxic inhibitory activity. Subsequent chemical investigation of this extract led to the isolation of seven new compounds ( 1 – 7 ) and 15 known analogues ( 8 – 22 ).…”
mentioning
confidence: 99%